1997
DOI: 10.1076/phbi.35.4.278.13309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Homonia riparia Lour. for Antiurolithiatic Activity in Albino Rats

Abstract: Ethanol extract of the roots of Homonia riparia was tested for its antiurolithiatic activity against calcium oxalate and magnesium ammonium phosphate stones in male albino rats. Calcium oxalate stones were induced by feeding 3% glycolic acid along with normal feed and magnesium ammonium phosphate stones were induced by implantation of zinc discs in the urinary bladder. The ethanol extract of H. riparia (2 g/kg/day, orally) was found to be effective in reducing deposition of calcium in the kidney of both prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[16] Urinary supersaturation with respect to stone-forming constituents is generally considered to be one of the causative factors in calculogenesis. Evidences in previous studies indicated that in response to 14 days period of ethylene glycol (0.75%, v/v) administration, young male albino rats form renal calculi composed mainly of calcium oxalate [6,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…[16] Urinary supersaturation with respect to stone-forming constituents is generally considered to be one of the causative factors in calculogenesis. Evidences in previous studies indicated that in response to 14 days period of ethylene glycol (0.75%, v/v) administration, young male albino rats form renal calculi composed mainly of calcium oxalate [6,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, root of the plant is used in India as a laxative, emetic, diuretic, to treat urinary calculi, syphilis, gonorrhoea, malaria, antiseptic, inflammation, ulcers, urinary discharges, urinary infection, hepatitis and fungal infections. [2][3][4] Six new cycloartane type triterepenes and quercetin glycoside have been isolated from the leaves of Homonoia riparia. β-sitosterol, stigmasterol, taraxerone, taxerol, lupenol, gallic acid, β-acetyl aleuritolic acid have been isolated from the heart wood and bark of Homonoia riparia.…”
Section: Introductionmentioning
confidence: 99%
“…This model is the most widely used model and has been more extensively reported in the scientific literature. This model represents the process of magnesium ammonium phosphate crystal growth [13][14][15] . Ethylene glycol is orally administered after implantation for the development of calcium oxalate stone 12 .…”
Section: Discussionmentioning
confidence: 99%